2005
DOI: 10.1097/01.ju.0000181805.30826.fa
|View full text |Cite
|
Sign up to set email alerts
|

Wound Complications After Hand Assisted Laparoscopic Surgery

Abstract: Our findings suggest that wound infections and hernias occur less frequently with HALS than with open surgery, but more often than with standard laparoscopy. Certain patient comorbidities (eg obesity), modifiable risk factors (eg smoking status) and procedural variables (eg omission of perioperative antibiotics or length of procedure) may adversely influence HALS wound complications. This information can be used to decide between HALS and standard laparoscopic approaches in particular patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 20 publications
2
31
1
3
Order By: Relevance
“…Montgomery et al [15] reported a slightly higher SSI rate of 5% for kidney surgery than our series. In the field of urology, SSIs occur more often compared to the SSI rates for all surgical specialties (5.6 vs. 1.5%) [5].…”
Section: Discussioncontrasting
confidence: 47%
“…Montgomery et al [15] reported a slightly higher SSI rate of 5% for kidney surgery than our series. In the field of urology, SSIs occur more often compared to the SSI rates for all surgical specialties (5.6 vs. 1.5%) [5].…”
Section: Discussioncontrasting
confidence: 47%
“…Some studies also have shown that the wound complication rate is lower with laparoscopic surgery, including the rate for incisional hernias [13][14][15][16][17][18][19][20][21]. However, we could find no literature evaluating extraction-site incisional hernias after LCS with respect to midline versus off-midline incisions.…”
Section: Introductionmentioning
confidence: 93%
“…The results indicate a marked impact of antibiotic prophylaxis but no other study confirms the data. In one report on surgical site infections (SSI) in which antibiotic prophylaxis was not in the protocol, Montgomery reports wound infections in 6.8% (range 5.0-7.9%) in clean and clean-contaminated hand-assisted kidney surgery, with no difference whether the urinary tract was opened or not [66]. In one study of clean surgery in patients with or without a risk factor for SSI, antibiotic prophylaxis had no impact in low-risk patients whereas it reduced the frequency in patients with at least one risk factor [67].…”
Section: Clean Operationsmentioning
confidence: 96%